Characterization of DNA Methylomic Signatures in Induced Pluripotent Stem Cells During Neuronal Differentiation - Imm, Jennifer; Pishva, Ehsan; Ali, Muhammadd; Kerrigan, Talitha L.; Jeffries, Aaron; Burrage, Joe; Glaab, Enrico; Cope, Emma L.; Jones, Kimberley M.; Allen, Nicholas D.; Lunnon, Katie (Frontiers in Cell and Developmental Biology, 2021)
In development, differentiation from a pluripotent state results in global epigenetic changes, although the extent to which this occurs in induced pluripotent stem cell based neuronal models has not been extensively characterized. In the present study, induced pluripotent stem cell colonies (33Qn1 line) were differentiated and collected at four time-points, with DNA methylation assessed using the Illumina Infinium Human Methylation EPIC BeadChip array. Dynamic changes in DNA methylation occurring during differentiation were investigated using a data-driven trajectory inference method. We identified a large number of Bonferroni-significant loci that showed progressive alterations in DNA methylation during neuronal differentiation. A gene-gene interaction network analysis identified 60 densely connected genes that were influential in the differentiation of neurons, with STAT3 being the gene with the highest connectivity.